THE EFFECT OF LEARNING START WITH A QUESTION METHOD ON STUDENTS’ SPEAKING ABILITY (A STUDY AT THE TENTH GRADE STUDENTS OF SMK NEGERI 1 SARUDIK) - dita widya panggabean (JURNAL LINER (Language Intelligence and Educational Research), 2018)
The objective of this research is to know whether there is a significant effect of learning start with a question method on students’ speaking ability at the tenth grade students of SMK Negeri 1 Sarudik. This research uses experimental method with pre-experimental research design; one group pre-test post-test design. The population is all of the tenth grade students which consist of 112 students. Technique sampling that used on this research is systematic purposive sampling and the number of the sample consists of 33 students. In collecting the data, the researcher uses observation sheet to get the data of the application of learning start with a question method and test to get the data of the students’ speaking ability. The researcher uses statistic process in analyzing by using t test formula. Based on the data that had been analyzed, the result of data analyzing showed that t count is higher than t table (t count 9 > t table 2.03). So, the hypothesis is accepted. It means that there is a significant effect of learning start with a question method on students’ speaking ability at the tenth grade students of SMK Negeri 1 Sarudik.